ANALYSIS OF THE WORKING SURFACE OF THE CONTACT WIRE ON THE RESULTS OF EXPERIMENTAL INVESTIGATIONS AT THE SITES OF THE LVIV RAILWAY - , А. М., Д. В., О. Ю., О. Я. (Municipal economy of cities. Series: «Economy science», 2017)
The state of the working surface of the contact wire in the experimental sections of both AC and DC is analyzed in the operation of an electric rolling stock equipped with different types of liners of current collectors. The photographs of the working surfaces of the contact wire are given in the article before the application of the new type of linings and after. Positive effect on the state of the working surface of the contact wire on the use of pantograph linings of a new type was noted. Keywords: electric locomotive, electric train, wear and tear, contact wire, current collector.